2014
DOI: 10.2174/1871527313666140228114456
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Interaction of Phycocyanin with β-Secretase: A Putative Therapy for Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) represents a neurological disorder, which is caused by enzymatic degradation of an amyloid precursor protein into short peptide fragments that undergo association to form insoluble plaques. Preliminary studies suggest that cyanobacterial extracts, especially the light-harvesting protein phycocyanin, may provide a means to control the progression of the disease. However, the molecular mechanism of disease control remains elusive. In the present study, intact hexameric phycocyanin was is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Moreover, Singh et al has reported the crystal structure and in silico affinity of PC αβ dimer with β-secretase ( Figure 5), the potential drug target for Alzheimer's disease [41]. The same was also evidenced experimentally by using the Alzheimer model C. elegans CL4176 [41].…”
Section: Pbps As Anti-aging Moleculesmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, Singh et al has reported the crystal structure and in silico affinity of PC αβ dimer with β-secretase ( Figure 5), the potential drug target for Alzheimer's disease [41]. The same was also evidenced experimentally by using the Alzheimer model C. elegans CL4176 [41].…”
Section: Pbps As Anti-aging Moleculesmentioning
confidence: 65%
“…1FKN is found to dock in close proximity of the β-subunit while the 3UQP is found to dock in an α-subunit proximal location. (Adapted from Singh et al [41].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…A09DM) in wild type and transgenic Caenorhabditis elegans (C. elegans) ( Figure 6). Singh et al [63] (2014) have recently given the putative therapy of Alzheimer's disease (AD) by in silico molecular docking between the structures of PC and βsecretase (molecule assumed to Sonani RR et al . Purification, production and applications of PBPs be possible drug target for AD) ( Figure 6C).…”
Section: Pharmaceutical and Neutraceuticalmentioning
confidence: 99%
“…A: Phycoerythrin-feeding increases the mean life span of wild type N2 C. elegans in dose-dependent manner [43] ; B: Phycoerythrin-feeding increases mean survival percentage of C. elegans in under normal and oxidative (paraquat) stressed conditions [43] ; C: PE-treatment moderates the heat-induced Alzheimer associated paralysis in the muscles of CL4176 C. elegans [63] ; D: Representative images of CL4176 animal grown at 16 ℃, at 25 ℃ and at 25 ℃ with phycoerythrin. Phycoerythrin effectively moderates the Alzheimer associated phenotype in CL4176 C. elegans [63] . PE: Phycoerythrin; C. elegans: Caenorhabditis elegans.…”
mentioning
confidence: 99%
“…Especially, the phycobiliproteins (PBPs) are the major metabolic product and harvest the sunlight for photosynthesis in cyanobacteria. PBPs are widely used in food, cosmetics, and biomedical industries due to their unique color; amino acid composition; and other imperative biological properties including anticancer, antiinflammatory, and hepatoprotective activities (Sonani et al 2014aLiu et al 2000;Singh et al 2014;Kumar et al 2015;Rimbau et al 1999;Riss et al 2007;Romay et al 2003;Bei et al 2000).…”
mentioning
confidence: 99%